THE PROCESS OF ADAPTING AND REINTERPRETING SHAKESPEARE'S WORKS FOR DIFFERENT CULTURAL CONTEXTS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
Adapting and reinterpreting Shakespeare's works for various cultural contexts involves a complex process of translating not only language but also themes, settings, and character dynamics to resonate with diverse audiences around the world. This process underscores the universality of Shakespeare's narratives while highlighting the unique perspectives and values of different cultures.